2007
DOI: 10.2193/2006-354
|View full text |Cite
|
Sign up to set email alerts
|

Does Management for Duck Productivity Affect Songbird Nesting Success?

Abstract: Habitat management for ducks has significantly influenced prairies and wetlands used by other species. However, the effects of management on other species have not been clearly assessed. We present the first study to compare the nesting success of ducks with the productivity of coexisting passerines. We evaluated effects of cattle grazing, subdivision of fields, habitat edges, year, and vegetation structure on duck and songbird nesting success in 32 mixed-grass prairie fields in southern Alberta, Canada. Duck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…The pastures and haylands of New York State (Norment et al 2010) and the intermountain semidesert region of British Columbia (Harrison et al 2010) differ from the Great Plains, where much of what is known about effects of livestock grazing on birds in North America originates. Nevertheless, Harrison et al (2010) and Norment et al (2010) concluded that livestock management is compatible with the conservation of a number of grassland bird species, consistent with many studies from the Northern Great Plains (e.g., Bareiss et al 1986, Kruse and Bowen 1996, Koper and Schmiegelow 2007.…”
supporting
confidence: 78%
“…The pastures and haylands of New York State (Norment et al 2010) and the intermountain semidesert region of British Columbia (Harrison et al 2010) differ from the Great Plains, where much of what is known about effects of livestock grazing on birds in North America originates. Nevertheless, Harrison et al (2010) and Norment et al (2010) concluded that livestock management is compatible with the conservation of a number of grassland bird species, consistent with many studies from the Northern Great Plains (e.g., Bareiss et al 1986, Kruse and Bowen 1996, Koper and Schmiegelow 2007.…”
supporting
confidence: 78%
“…Some of these can be tentatively rejected based on logic or the natural history of our focal species. First, increased parasitism and predation near agricultural edges is an unlikely cause because nesting success of grassland songbirds is often higher near edges in mixed-grass prairies (e.g., Davis 2004, Renfrew et al 2005, Koper and Schmiegelow 2007. We speculate that variation in microclimate due to edge effects, e.g., increased wind penetration (Mesquita et al 1999, Bollinger andGavin 2004) would be restricted to an area immediately adjacent to prairie edges; therefore, this mechanism seems unlikely to explain why some species avoided edges at great distances such as Chestnut-collared Longspur avoidance of crops, at least 1.95 km.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mixed-grass prairies are fragmented by juxtaposition to habitats that are structurally similar, including some that can provide suitable nesting habitat. For example, a wheat or canola cropland matrix surrounding mixed-grass prairie may not increase predation risk near edges (Davis et al 2006, Koper andSchmiegelow 2007, but see Horn et al 2005), and does not create a physical barrier to avian movement among mixedgrass fragments (Davis 2004, Renfrew et al 2005. Therefore, it is less obvious why mixed-grass prairie birds avoid habitat edges.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle may cause nest failure through trampling (Renfrew and Ribic 2003) and may even depredate nests (Nack and Ribic 2005). However, trampling and depredation rates in northern mixed-grass prairies are low (e.g., Koper and Schmiegelow 2007), presumably because stocking rates are typically low in these relatively arid regions. This suggests that the effects of livestock are generally indirect through the impact of livestock on vegetation structure (Sutter and Ritchison 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps surprisingly, the few studies that have examined the role of nest site vegetation structure and/or cattle grazing in songbird nest survival have found variable effects of cover on nest survival in that tall, dense vegetation may lead to either lower or higher nest survival (e.g., Davis 2005;Winter et al 2005;Jones and Dieni 2007;Koper and Schmiegelow 2007;Kerns et al 2010). Red-winged blackbird (Agelaius phoeniceus) and Savannah sparrow (Passerculus sandwichensis) nest survival was significantly higher in ungrazed pastures than in continuously grazed and rotationally grazed pastures in nonnative prairie in southwestern Wisconsin (Temple et al 1999).…”
Section: Introductionmentioning
confidence: 99%